Legal Consumerism Model in the Reconstruction of Consumer Protection Law - Sukendar, Sukendar; Carreon, Jonthan Rante; Purnomo, Singgih; Kuncoro, Aditya Bagus (Eastasouth Institute, 2025)
The existing legal framework for consumer protection in Indonesia has not been able to respond adaptively and integratively to the challenges of the digital economy era, including cross-border issues, algorithm governance, and consumer empowerment, resulting in a gap between regulation and actual protection needs. To develop a legal consumerism model that integrates adaptive regulation, technology-based law enforcement, and consumer empowerment to reconstruct Indonesia’s consumer protection law so that it is responsive to the dynamics of the digital market and ASEAN regional integration. This study employs a normative–conceptual approach integrating doctrinal legal analysis, comparative jurisdiction review, and conceptual exploration of literature, policies, and best practices to qualitatively design an integrative, adaptive, and participatory legal consumerism model that reconstructs consumer protection law in response to digital-era and regional market integration challenges. This research concludes that the Legal Consumerism model offers a transformative framework for reconstructing consumer protection law in Indonesia by integrating adaptive legal norms, technology-based enforcement, and consumer empowerment into a single, coherent system. Philosophically anchored in distributive and corrective justice, ontologically recognizing consumers as active legal subjects, and teleologically oriented toward a sustainable digital market ecosystem, the model bridges the normative–empirical gap that has long hindered effective protection. By synthesizing lessons from Indonesia, Thailand, and ASEAN’s regional frameworks, this concept not only addresses structural weaknesses in current regulations but also anticipates emerging risks from algorithmic pricing, cross-border transactions, and digital data governance, thereby positioning consumer protection as both a legal safeguard and a driver of trust in the modern economy.